The Impact of Intraoperative CT-Based Navigation in Congenital Craniovertebral Junction Anomalies: New Concepts of Treatment - Giorgio Cracchiolo; Ali Baram; Gabriele Capo; Zefferino Rossini; Marco Riva; Andrea Fanti; Mario De Robertis; Maurizio Fornari; Federico Pessina; Carlo Brembilla (Brain Sciences)
Background: Congenital craniovertebral junction anomalies (CCVJAs) encompass a diverse range of conditions characterized by distorted anatomy and significant variation in the pathways of neurovascular structures. This study aims to assess the safety and feasibility of tailoring posterior fixation for CCVJAs through intraoperative CT-based navigation. Methods: An in-depth retrospective analysis was conducted on eight patients diagnosed with CCVJAs (excluding Arnold–Chiari malformation). These patients underwent posterior fixation/arthrodesis facilitated by intraoperative CT-based navigation. The analysis included an examination of the fixation strategies, complication rates, length of stay, post-operative complications, and success of arthrodesis. Additionally, a comprehensive literature review was undertaken to contextualize and compare our findings. Results: Patients undergoing CVJ posterior fixation with intraoperative CT-based navigation exhibited a flawless record, devoid of complications related to the damage to neurovascular structures, as well as any instances of screw misposition, pullout, or breakage (0 out of 36 total screws). Furthermore, the entire cohort demonstrated a 100% arthrodesis rate. None of the patients required treatment with an occipital plate. Conclusions: The incorporation of intraoperative CT-based navigation proves to be an invaluable asset in executing CVJ posterior fixation within the context of CCVJAs. This technology facilitates the customization of posterior constructs, a crucial adaptation required to navigate the anatomical challenges posed by these anomalies. The secure placement of screws into the occipital condyles, made possible by navigation, has proven highly effective in achieving CVJ fixation, obviating the need for an occipital plate. This technological leap represents a significant advancement, enhancing the safety, precision, and overall outcomes for patients undergoing this surgical procedure, while concurrently reducing the necessity for more invasive and morbid interventions.